A Proposed Framework to Support the Competitive Advantage of Mobile Phone Service Companies in the Kingdom of Saudi Arabia - Mohamed A. Amin; Mohamed M. Elmetwaly; Amira S. Elshorbagy; Moustafa A. Elnadi; Elsayed K. Mohamed; Mahmoud Abdelaziz Elmansi; Amira Mohammed Ahmed; Khalid Yousif Ibrahim Salih (Migration Letters, 2023)
This research aimed to determine the relationship between customer knowledge management and competitive advantage through mediating innovative ability, applied on companies of mobile phone services. The structural equation modelling was used to measure this relationship. A quantitative method was chosen using the deductive approach in this research. To analyze the primary data, AMOS statistical software was used to measure the direct, indirect, and total effects between research variables. The sample size was 229 units. The results showed that there was a positive significant correlation between customer knowledge management, innovative ability, and competitive advantage. It also showed that there was a positive significant effect of customer knowledge management on innovative ability, and competitive advantage. It also indicated a positive significant effect of innovative ability on competitive advantage. It was also found that innovative ability significantly mediates the relationship between customer knowledge management and competitive advantage.